Audiovisual language, multiliteracies, and innovation: ccollaborative possibilities for the school environment - Freire, Maximina M.; Sá, Cristiane Freire de (The ESPecialist, 2024)
This article discusses the importance of audiovisual language in the production of educational videos, with multiliteracies as a possibility for pedagogical innovation. Wohlgemuth (2005) and Priuli (2017) problematize the production of educational videos, considering the perspective of an essentially pedagogical production, breaking the reproducibility established by the media industry. Ribeiro (2016) and Rojo and Moura (2019) investigate deeper into the issue, emphasizing the inclusion of educators in the production processes. In this sense, this article discusses the importance of teachers and students increasing their proficiency in audiovisual language from a multi-learning perspective, placing social practices as central to promoting innovative, collaborative and co-authored pedagogical processes. These processes are illustrated by some strategies based on collaborative principles as inspiration for innovative practices in educational audiovisual production.